Fractional generalization of Rodrigues-type Formulas for Certain Class of Special Functions (European Journal of Pure and Applied Mathematics, 2015)
This paper refers to some generalizations of certain classical Rodrigues formulas.By means of the Riemann - Liouville operator of fractional calculus Rodrigues-typerepresentation formulas of fractional order are derived and some of their properties aregiven and compared with the corresponding properties of known cases